K-Portal For Knowledge Sharing And Transfer Between Lecturers In Kolej Shahputra, Kuantan - Abu Azam, Hanisah (2009)
The proposed knowledge portal called KSP K-Portal tries to capture lecturer\'s knowledge in a more structured environment. Five main components are included in the portal.